Media Baru dan Partisipasi Politik (Pengaruh Twitter Terhadap Tingkat Partisipasi Politik Remaja dalam Pilkada Serentak 2015 pada Mahasiswa Fakultas Ilmu Komunikasi dan Informatika Universitas Muhammadiyah Surakarta Angkatan 2014) - Novalinda Viani, Afindiary; , Budi Santoso, S.Sos, M.Si (2017)
In democracies, general election is still regarded as the most concrete form of the community participation in governance, in a democratic country that is Indonesia. One of the media which is considered to increase the level of political participation of voters is microblogging, one of them is twitter. This study aims to investigate the influence of microblogging media twitter on the level of political participation in local elections teenagers simultaneously in 2015 among students of faculty of Communication Sciences and Informatics Department of Communication Studies University of Muhammadiyah Surakarta force in 2014. The author uses a quantitative method with direct field surveys, and the collection of data by using a questionnaire to a sample that is determined, namely, 63 respondents. Data analysis techniques used in this study is a simple linear regression analysis. From the test results, obtained value of the constant and variable regression participation of teens rate amounted to 9.558. While the regression coefficient of variable use of microblogging networking media twitter positive value that is equal to 0.518. T value of 2.993 is greater than the value t_table amounted to 1,998. It can be concluded that Ho refused and Ha is received, this indicates that the magnitude is significant relationship between the variables of use of microblogging networking media to variable participation rate of teenagers by 12.8% to 87.2% while the rest influenced by other variables.